Kualitas Visual Fasad Bangunan Bersejarah Jalan Hassanudin Kota Batu - Rahadian Nugroho; Jenny Ernawati; Joko Triwinarto (RUAS, 2021)
Relics of buildings with Dutch colonial architecture to this day can still be found in several road corridors, especially in Pesanggrahan Village, one of which is Jalan Hassanudin, Batu City. This study serves to measure and measure the community towards building units in forming the image of the area on the corridor of Jalan Hassanudin. This research uses the imageability factor which is used to see the character of the area consisting of impressions, past memories, unforgettable memories, uniqueness, attractiveness, clarity, enjoyment and uniqueness. The measuring instrument used is the semantic differential scale of previous research references. The results of the research regarding impressions are the most dominant variable based on people's impressions. impressiveness, uniqueeness, atractiveness, clarity, pleasantness, distinctiveness, recognizableness are significant variables to the image of the historical area in the corridor of Jalan Hassanudin. Meanwhile, variables such as unforgettable memory and remembrance of the past are variables that have a sig value. > 0.05 so that it does not affect the image of the area.